Pregnancy diagnosis in goat by using vaginal cytology and trans-abdominal ultrasonography - Md. Aziz Ali; Md. Faruk Islam; S M Latifur Rahman; Begum Fatema Zohara (The Korean Society of Animal Reproduction and Biotechnology, 2020)
The present study was conducted in a goat farm for pregnancy diagnosis by using vaginal cytology and B-mode real time ultrasound using 5 MHz probe by transabdominal method. Seventeen pregnant does were used for this study. The objective of the study was to determine the earliest day of pregnancy and describe the chronological characteristics of pregnancy from day 22 to day 40 for vaginal cytology and day 25 to day 60 for ultrasonography of gestation. The differences among the average percentage of cell value in different age of pregnancy were significant (p < 0.05). The average percentage of intermediate cells (81.12%) was also significantly (p < 0.05) higher than superficial (9.41%), keratinized (7.10%) and neutrophil (2.61%) on 22-40th days of pregnancy. In case of real time B-mode ultrasonography, the gestational sac was observed only in three does out of seventeen (17.6 %) at 25-30 days whereas the placentomes and heart beat of the foetus were first detected at 31-35 days in six does (35.3%). The foetal leg buds were first visualized at 36-40 days in four does (23.5%) whereas the foetal vertebral column was first observed at 36-40 days of gestation in only three does (17.6%). In conclusion, vaginal cytology and trans-abdominal ultrasonography can be used for detection of early pregnancy in does.